2018
DOI: 10.1097/md.0000000000013575
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transabdominal preperitoneal technique versus open surgery with the ULTRAPRO Hernia System for the repair of female primary femoral hernias—an observational retrospective study

Abstract: Femoral hernias (FHs), predominantly seen in females, require surgery for cure. To date, surgical repair of primary FHs in female patients with either open surgery or laparoscopic operation has been poorly documented. We retrospectively investigated the treatment of female primary FHs with open surgery using the ULTRAPRO Hernia System (UHS procedure) or the laparoscopic procedure, namely, the transabdominal preperitoneal (TAPP) technique. A total of 41 female patients with primary FHs who had undergone UHS or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Endoscopic procedures have been shown to be safe and effective for the repair of inguinal and femoral hernias. 18,[22][23][24] Additionally, clinical studies comparing endoscopic procedures versus open surgery for groin hernia repair have revealed that endoscopic procedures, namely, TAPP repair and total extraperitoneal techniques, result in a lower wound infection rate, faster recovery and return to normal activities/work, and a lower incidence of chronic pain. [25][26][27][28] However, no studies to date have investigated the anatomical localization of MCURLs relative to the inguinal canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic procedures have been shown to be safe and effective for the repair of inguinal and femoral hernias. 18,[22][23][24] Additionally, clinical studies comparing endoscopic procedures versus open surgery for groin hernia repair have revealed that endoscopic procedures, namely, TAPP repair and total extraperitoneal techniques, result in a lower wound infection rate, faster recovery and return to normal activities/work, and a lower incidence of chronic pain. [25][26][27][28] However, no studies to date have investigated the anatomical localization of MCURLs relative to the inguinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…A space between the inner ring of the inguinal canal and the triangle of doom was created by dissection, and a 10- × 15-cm polypropylene hernia patch covering the entire myopectineal orifice was placed and fixed in this space as described elsewhere. 18 When the distal end of the cyst extended beyond the inner ring and was difficult to resect with the TAPP procedure, the residual lesion was further excised by open surgery as described previously. 2 Briefly, an incision starting from the external ring and extending toward the inner ring of the inguinal canal was made to open the skin, subcutaneous tissue, and external oblique aponeurosis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, TAPP is associated with reduced postoperative pain and early restoration of normal activities. 5,6 Therefore, TAPP seems an appealing technique for female with femoral hernia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, little is known about the role of most ligaments and other soft tissues of the anterior pelvic ring, in spite of these structures gaining recent attention in the literature, particularly in relation to abdominal and gynecological surgery (Becker et al, 2010). With respect to the anterior pelvic ring, the soft tissues of the superior pubic ramus including the thick periosteum and fascial structures serve as anchor points in hernia repair as well as in urinary antiincontinence operations and neovaginal reconstruction (Burch, 1961;McVay, 1974;Perdu et al, 1998;Chen et al, 2018). Such thickened connective tissue was originally described by Cooper as "a ligamentous expansion, which forms a remarkably strong ridge above the iliopectineal line" (Cooper, 1804).…”
Section: Introductionmentioning
confidence: 99%